ALTERNATIVES FOR PSYCHOLOGICAL ILLNESS TREATMENT AND PREVENTION IN MALAYSIA FROM THE PERSPECTIVE OF SHARIAH - Muneer Ali Abdul Rab; Abdul Manan Ismail; Hamidin Awang; Mesbahul Hoque; Nasser Ahmad Aljabri; Abdullah Ali Salim AlShibli (Malaysian Journal of Syariah and Law, 2022)
Scientific studies have revealed that a large percentage of Malaysian society suffers from psychological disorders such as depression, anxiety, stress, schizophrenia and others, which is the biggest health problem among Malaysians after heart disease. The aim of this study is to explain the reasons for the prevalence of these psychological illnesses and to analyse the prevention methods, approaches and treatment of psychological illnesses according to Shariah scholars and then to show a therapeutic and preventive approach to psychological illnesses according to Shariah, using the inductive and analytical approach. The study concluded that psychiatrists have not clarified the exact causes of mental illness, but they suggested that they are the result of genetic, biological, environmental and psychological factors. Among the reasons mentioned by Shariah scholars are love of the world, committing sins, distance from Allah S.W.T., ignorance of religion, isolation, family and environment. The therapeutic and preventive model for contemporary psychological illnesses in Malaysia consists of the following methods such as seeking Islamic knowledge, belief in Allah S.W.T and the Last Day, patience and striving for reward, good deeds, good company, reading the Quran, reflecting on it and acting upon it (the Quran), remembrance and gratitude to Allah S.W.T., prayings on the Messenger of Allah S.W.T., supplication, treatment with legal ruqyah and psychological medicine, striving to eliminate the causes that cause sorrow and reaching the causes that cause joy. There are studies and testimonies from psychiatrists that confirm these methods and prove their effectiveness in preventing and treating mental illness. The study also contains important recommendations for the parties concerned in this matter.